A dinâmica da família nuclear como influência na criação e constituição da psicose - Kuczynski, Julia Youssef (2010)
The present work aims to understand the intersubjective relationship of family structure as an influence in the creation and constitution of the psychosis of one or more of its members. Taking into account this objective, we focus on the major psychoanalytic concepts proposed by Freud and Lacan, specifically the concepts of individual constitution and its implications. The postulates of psychosis and family will be subsidized both by psychoanalysis and by authors of system theory, as Bateson, Watzlawick and Jackson. Once presented the theory on the individual constitution, will be discussed a case study of a family of a psychotic patient from the Hospital das Clínicas’ (Clínicas Hospital) psychotherapy service through a semi-directed interview and the Rorschach method